2006
DOI: 10.1111/j.1365-2672.2006.02939.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bacterial community during fermentative hydrogen and acid production from organic waste by thermophilic anaerobic microflora

Abstract: Aims:  Changes in fermentation pattern during the treatment of organic wastes containing solid materials by thermophilic anaerobic microflora were investigated with respect to product formation and bacterial community structure during hydrogen production. Methods and Results:  Anaerobic microflora enriched from sludge compost was cultivated using artificial garbage slurry in a continuous flow‐stirred tank reactor. Product formation varied depending on pH and hydraulic retention time (HRT) applied. Community an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 32 publications
7
33
0
1
Order By: Relevance
“…In general, production of these two acids favors the production of hydrogen, according to Eqs. (5) and (6) [44]. Theoretically, four moles of hydrogen are produced from glucose concomitantly with 2 mol of acetate:…”
Section: Confirmation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, production of these two acids favors the production of hydrogen, according to Eqs. (5) and (6) [44]. Theoretically, four moles of hydrogen are produced from glucose concomitantly with 2 mol of acetate:…”
Section: Confirmation Experimentsmentioning
confidence: 99%
“…There have been many reports indicating that Thermoanaerobacterium spp. possess the capability to utilize complex carbohydrate such as starch, xylan, cracked corn, cellulose and simple sugar accompanied with hydrogen and acid production [41][42][43][44][45]. Several species of Thermoanaerobacterium are known for their hydrogen production characteristics, including T. thermosaccharolyticum, T. polysaccharolyticum, T. zeae, T. lactoethylicum and T. aotearoense.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…3), which indicates that there was a lag time to reestablish the microbial communities in response to the event ii. It has been reported that operational periods of at least threefold of the HRT are required for the turnover of the supplied wastewater (Ueno et al 2006. Taken together, the dynamics of the microbial diversity indices and finescale microbial community structure based on the weighted UniFrac distances were apparently correlated with the reactor performance, especially the COD removal ratio.…”
Section: Discussionmentioning
confidence: 94%
“…They have been identified as H 2 -producing bacteria in mixed cultures, under thermophilic conditions [9,47,48]. Several species of the genus Thermoanaerobacterium are known for their ability to produce H 2 , mainly T. saccharolyticum and T. thermosaccharolyticum [9,31].…”
Section: Microbial Community Analysismentioning
confidence: 99%